2013
DOI: 10.1016/j.prro.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the role of case-oriented peer review to improve quality and safety in radiation oncology: Executive summary

Abstract: This report is part of a series of white papers commissioned for the American Society for Radiation Oncology (ASTRO) Board of Directors as part of ASTRO's Target Safely Campaign, focusing on the role of peer review as an important component of a broad safety/quality assurance (QA) program. Peer review is one of the most effective means for assuring the quality of qualitative, and potentially controversial, patient-specific decisions in radiation oncology. This report summarizes many of the areas throughout rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 9 publications
1
143
0
2
Order By: Relevance
“…For instance, incident learning should include the issue of error disclosure and professional aspects 30. Principles of error proofing (Table 1 & 2, for example, barrier analysis, QA, and automatic error detection) could be modified to have less of a physics focus, and quality audits could be modified to focus less on commissioning and phantoms and more on issues like physician peer review 31, 32. Adapting aspects of the curriculum may also be of interest to graduate or certificate program directors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, incident learning should include the issue of error disclosure and professional aspects 30. Principles of error proofing (Table 1 & 2, for example, barrier analysis, QA, and automatic error detection) could be modified to have less of a physics focus, and quality audits could be modified to focus less on commissioning and phantoms and more on issues like physician peer review 31, 32. Adapting aspects of the curriculum may also be of interest to graduate or certificate program directors.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that peer review is recognised as having potential benefits, the issues of what to review and in what detail have not been fully defined. The American Society for Radiation Oncology have provided guidance on important parameters for peer review in the white paper by Marks et al [7]. Components of the pathway culminating in delivery of radiotherapy were graded 1e3 in terms of importance, according to potential risk to patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthcare setting, quality assurance refers to the analysis of each component of the patient pathway to identify failings, with the goal of ensuring safe, consistent, excellent standards of care for all patients. The non-clinical components in the patient pathway, such as waiting times and radiotherapy machine parameters, have well-documented, quality assurance practices monitoring their outcomes and safety [7]. In the delivery of curativeintent lung cancer radiotherapy, clinical oncologists are directly responsible for supervising the entirety of the patient's treatment pathway, from advising regarding the appropriateness of radiotherapy and identifying treatment volumes through to reviewing the patient's radiotherapy plan and clinical follow-up after radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Brundage et al (1999) identified that insufficient target volumes were one of the common reasons for treatment plan modification. In order to tackle this, in clinical practice, peer review is the proposed approach to decrease the probability of such (and other) human errors (Marks et al 2013;Mackenzie et al 2016;Brunskill et al 2017). In short, it is expected that the smaller the variations among physicians are, the fewer errors there are.…”
Section: Inter-observer Variation Among Outcomesmentioning
confidence: 99%